Analysis of Puccinia graminis f.sp. tritici Virulence and Reaction of Wheat Varieties to Virulent Races in Tigray - Teklay Abebe; Getaneh Woldeab; Woubit Dawit (Pest Managment Journal of Ethiopia, 2023)
Wheat stem rust caused by Puccinia graminis f.sp. tritici is amongst the biotic factors which cause up to 100% yield loss during epidemic years. The highland of Ethiopia is considered as a hot spot area for the development of stem rust. Hence, this study was carried out to detect the virulence diversity of P. graminis f. sp. tritici in Southern Tigray, and evaluate the seedling reaction of commonly grown wheat varieties to virulent stem rust races. The findings of this research were based on race analysis through inoculation of stem rust populations, isolation and multiplication of singlepustule of the pathogen and race determination by inoculating on the standard set of stem rust differential hosts; and testing eleven wheat varieties to three virulent races at seedling stage in a greenhouse. The phenotypic characterization of P. graminis f. sp. tritici resulted in identification of 20 races from 32 isolates, which included the most prevalent races TTSNK, RRJJC and HRJJC with a frequency of 9.4% each and the most virulent races TTKSK and TTSSK each making 85% of Sr genes ineffective. Among 20 wheat stem rust differential hosts, four were found effective for 75% and more of the races identified. Differential host carrying Sr24 was effective to all, while gene SrTmp was effective to 90% of the races followed by S ri7 and Sr31 (75% each). In contrast, differential hosts carrying SrMcN, Sr9b, Sr9g and SrlO were ineffective to 96.9, 93.8, 87.5 and 81.2% of the isolates tested, respectively. On the other hand, of the eight bread wheat varieties evaluated against three virulent races, more than 85% were susceptible to one or more of these races. Varieties Tura, Shina and Kubsa were susceptible to the three (TTKSK, TTSNK and RRTTF) races and TTSNK was virulent to all tested except variety Digalu. In contrast, the durum wheat varieties Gerardo, Asasa and local landrace were resistant to all the races tested. Thus, use of resistant Sr genes( Sr24 and SrTmp) and landraces in single variety through gene pyramiding gives the variety with wider base of stem rust resistance.